2021
DOI: 10.2991/assehr.k.210525.020
|View full text |Cite
|
Sign up to set email alerts
|

Communication in Developing Digital Competence of Future Professionals

Abstract: Digital transformation of education requires a higher educational institution to change its approach to the formation of professional competencies of future professionals. Development of digital competence, with Communication being one of its components, is an important aspect. The article substantiates the approaches of scholars to the interpretation of digital competence, namely its component Communication and Cooperation. The European framework and standards of digital competence of citizens and educators, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The survey of 112 students studying foreign languages was conducted, and it was found that the level of digital literacy of philology students is insufficient (Henseruk et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The survey of 112 students studying foreign languages was conducted, and it was found that the level of digital literacy of philology students is insufficient (Henseruk et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Digital literacy is an important component necessary for the life and professional growth of modern man (Henseruk et al, 2021). Therefore, its improvement is a general trend of modernization of teacher training, in particular, philological subjects (Tsiupak, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation